Relationship Between Health Anxiety and Quality of Life in Elderly People with Chronic Diseases - Heni Kristiani; Ni Made Ayu Wulansari; Emilia Puspitasari Sugiyanto (PT Bukuloka Literasi bangsa, 2025)
Health anxiety is a condition in which a person has thoughts that there may be a threat to their health. Some of these fears and anxieties focus on health issues, such as the assumption of having a serious illness when in fact there is no health problem. The purpose of this study was to determine the relationship between health anxiety and the quality of life of elderly people with chronic diseases. This was a quantitative study using a cross-sectional method. There were 88 respondents in this study, who were selected using total sampling technique. Based on the results of the study, it was found that on average, elderly respondents did not have health anxiety and their quality of life tended to be good. The results of the analysis using the Spearman Rank test showed a significant result between health anxiety and quality of life with a value of 0.027 (p-value 0.05), indicating that health anxiety can affect the quality of life of elderly people with chronic diseases. The correlation coefficient analysis yielded a result of (-) 0.235, which means that the relationship is weak and negative. If health anxiety increases, quality of life will decrease, and conversely, if quality of life decreases, health anxiety will increase. The suggestion from this study is that the results can be used as a reference in addressing psychosocial problems in the elderly, especially health anxiety. Keywords: health anxiety, quality of life, elderly with chronic diseases